CPT Parameters of Loess Subsoil in Lublin Area - Krzysztof Nepelski; Agnieszka Lal (Applied Sciences, 2021)
Loess soils were created by the wind transporting particles with later or in parallel occurred protogenetic, syngenetic and epigenetic processes. As a result, various genetic processes affected loesses strength and deformability characteristics. The aim of the study is to estimate the main CPT parameters of loess subsoil in Lublin area according to divided facies. The subsoil in the area of the Nałęczowski Plateau, where Lublin is located, consists mainly of loess from aeolian and aeolian–diluvial facies, and in the deeper parts—from aeolian–alluvial facies. Most of the results obtained for the aeolian facies at the level of qc in the range from 4.5 to 8.0 MPa indicate that these soils are a good load-bearing substrate for building structures. Cone resistances mostly at the level of 1.5–4.0 MPa for the diluvial and alluvial facies confirm that these facies constitute less favorable foundation conditions. The reduced resistance results mainly from the increased water content in ground pores. It is especially the soils of the diluvial facies that provide unfavorable foundation conditions, as they occur near the surface. Genetic processes are a very important element that should be taken into account in engineering research.